The Task Content of Occupations - Luca Bittarello; Francis Kramarz; Alexis Maitre (Institute of Labor Economics (IZA), 2018)
This paper evaluates how an increase in the supply of skilled labor affects task assignment within and between occupations. Guided by a simple theoretical framework, we exploit detailed information about individual workers' tasks from multiple surveys to examine the impact of a twofold rise in the share of university graduates in the French workforce between 1991 and 2013. Our identification strategy uses variation in the change in the graduate share across local labor markets. We find that higher average educational attainment is associated with more routine, fewer cognitive and fewer social tasks within occupations and with fewer routine, more cognitive and more social tasks across occupations.
Keywords: J21; J24; J31; 330; task; supply shock; routine tasks; cognitive tasks; social tasks